Salty Crackers as Fortuitous Dosimeters: A Novel PSL Method for Rapid Radiation Triage - Maltar-Strmečki, Nadica; Vidotto, Monica; Della Monaca, Sara; Erceg, Ina; Fattibene, Paola; Vojnić Kortmiš, Maja; Quattrini, Maria Cristina; Bortolin, Emanuela (Frontiers in Public Health, 2021)
When a radiological and nuclear (R/N) emergency occurs, the categorization of individuals into those who are unaffected and those requiring medical intervention is a high priority. At times, a professional dosimeter is not available and therefore some common belongings may be used as fortuitous dosimeters. The preparation of these objects for the measurement should be such as to give the most accurate and precise results. This paper focused on the Photo-Stimulated Luminescence (PSL) response of salty crackers confronts the problem of sample preparation (mass, grain size), dose response and signal stability. The dose response was determined for doses up to 5 Gy, which allowed the calculation of the limit of detection. Additionally, the signal stability was investigated for samples irradiated with 0.3 Gy and 3 Gy. The observed decrease of the signal does not prevent the detection in the dose range typical for R/N emergency. The main dosimetric characteristics were investigated by using two different models of PSL readers equipped with single (infrared) or double (infrared, blue light) stimulation. The results indicated that the limit of detection can be improved by applying blue light stimulation. Moreover, strong correlation of the measurements performed in the two different instrument, as well as the rapidity of the analysis and the simplicity of the operations, suggest that this method can be suitable for a rapid radiation triage of a large number of civilians in a mass casualty event. The study was simultaneously conducted by two laboratories (Ruđer Bošković Institute, RBI, Croatia and Istituto Superiore di Sanità, ISS, Italy) involved in the BioPhyMeTRE project (grant No. G5684) supported by NATO Science for Peace and Security Programme.